Ensaios sobre demanda por energia elétrica, produtividade e eficiência no setor agrícola no Brasil e na América do Sul - Santos, Cícero Pierry Bezerra dos (2017)
This dissertation is composed of two studies that address the demand for electricity in rural areas and total factor productivity (TFP) with decomposition using the Malmquist index, where each chapter consists of an article. The first study analyzed the impacts of the expansionary policies and the water crisis in the reservoirs of the Brazilian hydroelectric dams in the demand for electricity in the rural environment of Brazil, through a historical analysis of the formation of the Brazilian energy matrix, the management of generation indicators Of electric energy and by the approach of the economic policies expansionist and its impact in the increase of the demand for electric power in the rural environment. Using the electric power demand function, with the econometric methodology of selection of Backward models, with variables lagged in 4 time periods and through the application of autoregressive moving average vectors with exogenous variables (ARMAX). It can be verified that the exogenous variables applied to the model, were relevant for the estimation. From the results obtained with the model used, it was estimated the demand for electric energy in Brazil from June 2014 to March 2016, remaining the values estimated within the range of significance of 5% in relation to the real values obtained in this period. The methodology was adequate to predict the monthly consumption of electricity in rural Brazil. The second chapter proposes to measure the effects of access to electricity on rural productivity in the countries of South America, with the application of the frontier function of stochastic production proposed by Battese and Coelli (1995), with a Cobb- Douglas with no technical progress, where it is observed that the electric energy is around the inefficiency with a rate of 17.30%, for the set of countries under study, and through the Malmquist index obtained the decomposition of the total factor productivity In two periods, with a complete analysis of the database 1990 to 2012 and part of this database with the period between 2000 and 2012, where in both cases the improvement of TFP was in most countries as a function of an increase Of the access to technology, among them the consumption and access to electric energy by the families residing in the rural environment of the countries of South America.